A comparative study between syringe-based and screw-based 3D food printers by computational simulation - Guo, Chao-Fan; Zhang, Min; Bhandari, Bhesh (Computers and electronics in agriculture, 2019)
•Computational simulated models were built for syringe and screw-based 3D printer.•A comparative study was carried out for syringe and screw-based printer based on fluid characteristics.•The screw-based printer’s fluid characteristics are more complex than syringe-based one.•Backflows were found at the gap between walls and the filament in the extrusion tube. Extrusion-based three-dimensional (3D) printing is an emerging technology which has a high application potential in food manufacturing processes. Screw and syringe-based printers are two kinds of extrusion-based 3D printing methods that have been widely studied and reported. The objective of present work was to compare these two different kinds of extrusion-based food 3D printing methods, in fluid flow characteristics and printing profile by computational simulation model and printing experiment. Analysis of simulated model suggested that the screw-based 3D food printer had a complex fluid characteristic, and some backflows were found at the gap between walls and the screw flights in the extrusion tube. Whereas, the syringe-based 3D food printer showed more simple fluid characteristics, which could be easy to adjust. Moreover, the experimental 3D printing suggested that the screw-based 3D food printer were not suitable for extruding the inks with high viscosity. Results in present work provides information for suitable printing method selection, a theoretical base and technical guide for further 3D printing studies and new printer designing.